A Facile Approach to α‐Keto Esters via Oxidative Esterification of α‐Amino Carbonyl Compounds. Issue 8 (4th July 2019) - Wang, Yong‐qiang; Zou, Jiao‐xia; Wang, Hui‐hong; Peng, Xue; Lu, Ying‐mei; Feng, Yi‐yue; Chen, Chen; Shi, Tao; Wang, Zhen
Abstract: A direct oxidative esterification of α‐amino carbonyl compounds by two kinds of hydroperoxides, for the synthesis of α‐keto esters has been developed. The reaction shows broad substrates scope and good functional group tolerance, even for the synthesis of bulkyl esters, and is free of metal catalysts and external additives. Notably, the inhibitor of protein tyrosine phosphatases (PTPases) could be successfully synthesized with our protocol. Abstract : Oxy‐direct : A direct oxidative esterification of α‐amino carbonyl compounds by various hydroperoxides, for the synthesis of α‐keto esters has been developed. The reaction shows a broad substrate scope and good functional‐group tolerance, even for the synthesis of bulky esters, while being free of metal catalysts and external additives.